Тирольский фестиваль - Арутюновна Асатрян, Мариам (Musical Armenia, 2010)
Musicolgist, Mariam Harutyuni Asatryan, who continues his magistracy degree in Italy writes the article “Tirol’s festival”. The article is about annual festival about Austria- Bayern small town Erl, that has been organized and directed by Goustav Koon for already twenty years. The author writes about the director, who always organizes his brave programs and thoughts in an excellent way.